Memory test system for piston steady-state temperature measurement. (5th January 2017) - Dai, Hui; Huang, Ronghua; Li, Guiquan; Tang, Jie; Huang, Sheng
Highlights: A memory test system has been developed. Signals are almost constant under a steady working condition. Memory test system has very high precision. Memory test system has been used for piston temperature measurement. Memory test system can reliably get piston temperature. Abstract: Regarding the high thermal load of piston in engines, a novel apparatus, memory test system (MTS), was designed for steady-state temperature measurement of piston. By heating MTS up to 100 °C and 120 °C respectively, a test was carried out to verify the system and measure its error. Considering poor working conditions in engine, the readings of MTS and thermal plugs were compared with each other through an engine test to confirm the reliability of MTS. Moreover, MTS was used to measure piston temperature under multiple working conditions. The results show that MTS has very high precision and reliability and is competent in multi-condition test. MTS is an effective tool to measure piston temperature.